2021
DOI: 10.1007/s10615-021-00801-3
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Practice Challenges of COVID-19: MSW Students’ Perceptions of E-Therapy and the Therapeutic Alliance

Abstract: The COVID-19 pandemic prompted a radical shift in social work practice. Overnight, social work intervention models provided in-person gave way to the utilization of Information and Communication Technologies to facilitate direct practice in virtual environments (e-therapy). Social work’s slow acceptance of e-therapy prior to the pandemic resulted in a lack of training for many social work practitioners and MSW student interns, who were required to make rapid transitions to using and operating in online environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
2
14
0
4
Order By: Relevance
“…As experience was gained, it was found that psychosocial aspects could be addressed during these remote sessions. Khan experience (Earle & Freddolino, 2021;Phillip et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As experience was gained, it was found that psychosocial aspects could be addressed during these remote sessions. Khan experience (Earle & Freddolino, 2021;Phillip et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The paper provides insight into the lived experiences of The major shift in the provision of clinical services for the unit was the expansion of telecounseling and a reduction in face-toface counseling. Telecounseling is not a new concept in medicine and has been used since the 2000s in genetic counseling (Beretrich et al, 2018;Trepanier & Allain, 2014) and other fields such as spinal cord injury rehabilitation , managing depression , and social work (Earle & Freddolino, 2021). In genetic counseling, telecounseling services were first implemented in breast cancer but later expanded to include other areas (Trepanier & Allain, 2014).…”
Section: What the Paper Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…To adapt to COVID-19, social work researchers are investigating therapeutic alliances through telehealth (Craig et al, 2021;Earle and Freddolino, 2021;Swenson et al, 2021). In our practices, we have found this option to be beneficial for supporting families.…”
Section: Ongoing Use Of Technology In Practicementioning
confidence: 99%